Influence of al particle size and firing profile on void formation in rear local contacts of silicon solar cells - Dressler, Katharina; Kratt, Martina; Voss, Philipp A.; Ebert, Stefanie; Herguth, Axel; Hahn, Giso (IEEE journal of photovoltaics, 2016)
In this paper, the influence of Al particle size and the applied firing profile on void formation in local rear contacts of wafer-based silicon solar cells is investigated. Samples with a passivated emitter and rear cell (PERC) rear, but without front metallization, were metalized with six different Al screen-printing pastes, i.e., both commercial and homemade, featuring different particle size distributions and fired in a rapid thermal processing furnace with different firing profiles. Voids were detected with scanning acoustic microscopy measurements, and the fraction of voids in rear local contacts was analyzed. It was shown that the heating phase of the firing process has the strongest influence on void formation. With slower heating, void formation could be reduced to a fraction lower than 5% of the local contact area. Furthermore, it was shown that Al pastes consisting of a mixture of small and large Al particle sizes have a positive effect on the formation of voids.
Date of Publication: 29 October 2015
Gesehen am 27.04.2020